Intensity of anticoagulation and risk of thromboembolism after elective cardioversion of atrial fibrillation - Hellman T; Kiviniemi T; Nuotio I; Vasankari T; Hartikainen J; Lip GYH; Airaksinen KEJ (Elsevier, 2025)
Abstract
BACKGROUND:
Elective cardioversion (ECV) for atrial fibrillation (AF) is associated with a relatively low risk of thromboembolic complications. However, the optimal intensity of anticoagulation for ECV is unknown. We sought to assess the risk of thromboembolism in low (INR 2.0-2.4) vs. high (INR≥2.5) therapeutic range in a large retrospective cohort study.
METHODS:
This multi-centre "real world" study included 1424 ECVs in 1021 patients. The primary outcome was a stroke or a transient ischaemic attack (TIA) or a systemic embolus during the 30-day follow-up after ECV.
RESULTS:
Altogether 4 (0.3%) strokes, 2 (0.1%) TIAs and 2 (0.1%) bleeds were detected during the 30-day follow-up after ECV. No systemic emboli were detected. There were 2 deaths (0.1%), one associated with a stroke. Median time to stroke/TIA was 4 (IQR 9.5) days and the median CHA2DS2-VASc-score was 2 (IQR 1.25) among patients with thromboembolic events. Mean INR at ECV was 2.7 (SD 0.54) in the study cohort. Patients with INR 2.0-2.4 at ECV had more thromboembolic events compared with patients with INR≥2.5 (5/529 (0.9%) vs. 1/895 (0.1%), p=0.03). Comprehensive postprocedural INR data was available for 733 (71.8%) patients and 1007 cardioversions. At least one subtherapeutic (<2.0) INR value was detected within 21days after 230 (22.8%) ECVs and this drop in INR level was associated with a higher risk for thromboembolic events compared with continuous therapeutic post-cardioversion anticoagulation (1.7% vs 0.3%, p=0.03).
CONCLUSIONS:
Our results suggest that the intensity of periprocedural anticoagulation is associated with the risk of thromboembolic events after ECV.